Studies on the growth and characterization of CdS and PbS nanoparticles using sugar-ester nonionic water-in-oil microemulsion - Khiew, P.S.; Radiman, S.; Huang, N.M.; Ahmad, M.D.S. (2003)
The nanometer-sized semiconductors of CdS and PbS were prepared in the nonionic water-in-oil microemulsion system formed by sucrose monoester, 1-butanol, cyclohexane and water. The surfactant that has been employed in the present study is commercial food grade additive, in which is biodegradable and nonhazardous to the environment. The resultant nanoparticles were characterized by X-ray diffraction measurements in order to determine the crystalline phase of the products. The structural and morphological features of the nanoparticles have been investigated by energy filter transmission electron microscopy, X-ray photoelectron spectroscopy and UV-Vis absorption spectroscopy. The experimental results showed that the synthesized nanoparticles exhibited strong quantum confinement effect as the optical band gap increased significantly as compared to the bulk molecules. In addition, the as-prepared nanoparticles were found in spherical shape with a reasonably narrow size distribution. Â© 2003 Elsevier Science B.V. All rights reserved.